A brief overview of current status of European spatial data infrastructures − relevant developments and perspectives for Bulgaria. Issue 2 (3rd April 2017) - Pashova, Lyubka; Bandrova, Temenoujka
Abstract: The paper aims to present a concise overview of the current status of the national spatial data infrastructures (SDI) of the European Union (EU) member states combined with specific peculiarities for Bulgaria. Some major challenges within the progress of the EU SDIs establishing, which is regulated by the European Directive INSPIRE (Infrastructure for spatial information in Europe) toward establishment of a SDI for environmental policies and activities, are marked out. Available comparative analyses of the main indicators for metadata, data-sets, and data services provided by EU member states are briefly discussed as a special attention is given to the Bulgarian progress. Recent achievements on accelerating the process of implementing the recommendations of the INSPIRE Directive in Bulgaria are outlined.